The Effect of E-Wallet Application Use and Financial Literacy on Students' Financial Management - Sukmawati, Sukmawati; Asriany, Asriany; Ramadhan, Abid (PT. EQUATOR SINAR AKADEMIA, 2025)
Technology can make financial activities easier. However, this must be balanced with good financial literacy so as not to cause consumptive behavior in the use of financial technology. This study aims to determine the effect of the use of e-wallet applications and financial literacy on financial management. The sampling technique used is purposive sampling. The population is class A finance students of Muhammadiyah University of Palopo and the sample is 118 students using a questionnaire distributed via google form. The research method uses a quantitative approach through multiple linear regression analysis and is processed with the help of SPSS. The results of this study indicate that the variables of e-wallet use and financial literacy have a positive and significant effect on financial management in students.